Training to Prove the Area of Circle Using Manipulative Media through Mathematics Learning Assistance: Pelatihan Pembuktian Luas Lingkaran dengan Media Manipulatif melalui Pendampingan Belajar Matematika - Baharuddin; Ahmad Zaki; Khadijah; Asmaun (Yayasan Ahmar Cendekia Indonesia, 2024)
Circles are a part of mathematics that is often found in the surrounding environment. However, the circle is still quite a difficult challenge for students, so many still get relatively low grades. The aim of this activity is to provide understanding and meaningful learning experiences to students in learning mathematics, namely proving the area of ​​a circle using manipulative media. The data collection method is a survey by giving questionnaires to students after the activity and documentation in the form of photos of the activity. The subjects of service were 40 class VIII students at Marioriawa 1 Middle School, Soppeng Regency. The results of the questionnaire showed that on average students responded >90% to all statements given, meaning that learning activities using manipulative media made students more confident in solving mathematics problems, especially the area of ​​circles and developed students' skills in solving problems. The final test results for students showed that there was a drastic increase in student scores compared to the initial test results. Abstrak Lingkaran merupakan salah satu bagian dari ilmu matematika yang sering dijumpai di lingkungan sekitar. Namun lingkaran masih menjadi suatu tantangan yang cukup sulit bagi siswa sehingga masih banyak yang memperoleh nilai tergolong rendah. Tujuan kegiatan ini yaitu memberikan pemahaman dan pengalaman belajar yang bermakna kepada siswa dalam pembelajaran matematika yaitu membuktikan luas lingkaran dengan media manipulatif. Metode pengumpulan datanya yaitu survey dengan memberikan angket kepada siswa setelah kegiatan berlangsung dan dokumentasi berupa foto kegiatan. Subjek pengabdian yaitu siswa kelas VIII di SMP Negeri 1 Marioriawa Kabupaten Soppeng yang berjumlah 40 orang. Hasil angket diperoleh bahwa rata-rata siswa memberi respon sebesar >90% pada semua pernyataan yang diberikan, artinya kegiatan pembelajaran dengan media manipulatif menjadikan siswa lebih percaya diri dalam menyelesaikan soal matematika khususnya luas lingkaran dan mengembangkan keterampilan siswa dalam memecahkan masalah. Hasil tes akhir pada siswa menunjukkan bahwa terjadi peningkatan secara drastis terhadap nilai siswa dibandingkan dengan hasil tes awalnya.